Cannabinoids in Chronic Pain: Therapeutic Potential Through Microglia Modulation - van den Hoogen, Nynke J.; Harding, Erika K.; Davidson, Chloé E. D.; Trang, Tuan (Frontiers in Neural Circuits, 2022)
Chronic pain is a complex sensory, cognitive, and emotional experience that imposes a great personal, psychological, and socioeconomic burden on patients. An estimated 1.5 billion people worldwide are afflicted with chronic pain, which is often difficult to treat and may be resistant to the potent pain-relieving effects of opioid analgesics. Attention has therefore focused on advancing new pain therapies directed at the cannabinoid system because of its key role in pain modulation. Endocannabinoids and exogenous cannabinoids exert their actions primarily through Gi/o-protein coupled cannabinoid CB1 and CB2 receptors expressed throughout the nervous system. CB1 receptors are found at key nodes along the pain pathway and their activity gates both the sensory and affective components of pain. CB2 receptors are highly expressed on, and critically modulate the activity of, microglia, astrocytes, and peripheral immune cells. Expression of CB2 receptors on these central and peripheral immune cells is upregulated in chronic pain states and their receptor activity influences intracellular communication between immune cells and the surrounding neuronal circuitry. Interventions that alter this communication by targeting the CB1 or CB2 receptor improve pain outcomes in a variety of preclinical pain models. In this mini-review, we will highlight recent advances in understanding how cannabinoids modulate microglia function and its implications for cannabinoid-mediated analgesia, focusing on microglia-neuron interactions within the spinal nociceptive circuitry.